Testosterone and Cortisol Responses to Hiit and Continuous Aerobic Exercise in Active Young Men - Cofre-Bolados, C; Herrera-Valenzuela, T; Orihuela-Diaz, P; Reuquen-Lopez, P; Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
It is well known that physical exercise modifies plasma levels of testosterone and cortisol. However, the effect of high-intensity interval training (HIIT) on the plasma hormone levels is controversial. The aim of the study was to compare the effects of HIIT exercise or submaximal continuous aerobic exercise on circulating testosterone and cortisol levels in active male collegiate students. Methods: Thirteen moderately-active young adult males (20.2 (SD 2.1) years old) completed a HIIT (20 min of 15 s intervals of running at 110% of maximum oxygen consumption interspersed with 15 s of active rest at 40% of maximum oxygen consumption) and a continuous aerobic exercise (AEE) 20 min at 70-75% of maximum oxygen consumption. The mean total workload of both protocols was the same for each exercise session. Blood samples were collected pre-session (rest), immediately after the session (0 h), and 12 h post-session (12 h). Results: Both exercise protocols, similarly increased plasma levels of free testosterone immediately post-exertion (p < 0.05 AEE and p < 0.01 HIIT). No differences were observed between the conditions in the concentration of testosterone at 12 h. Cortisol level and Testosterone/Cortisol (T/C) ratio remained constant for all measurements, regardless of the type of exercise performed. Conclusion: The testosterone concentrations rose significantly post intervention in both HIIT and AEE condition, but 12 h post intervention there was no difference between conditions, decreasing to baseline (pre-intervention). The T/C ratio decreased significantly (below baseline) only in the HIIT condition 12 h post intervention. © 2019 by the authors.